Kinetochore stretching inactivates the spindle assembly checkpoint - Uchida, Kazuhiko S.K. (The Rockefeller University Press, 2009)
The spindle assembly checkpoint (SAC) monitors the attachment of microtubules to the kinetochore and inhibits anaphase when microtubule binding is incomplete. The SAC might also respond to tension; however, how cells can sense tension and whether its detection is important to satisfy the SAC remain controversial. We generated a HeLa cell line in which two components of the kinetochore, centromere protein A and Mis12, are labeled with green and red fluorophores, respectively. Live cell imaging of these cells reveals repetitive cycles of kinetochore extension and recoiling after biorientation. Under conditions in which kinetochore stretching is suppressed, cells fail to silence the SAC and enter anaphase after a delay, regardless of centromere stretching. Monitoring cyclin B levels as a readout for anaphase-promoting complex/cyclosome activity, we find that suppression of kinetochore stretching delays and decelerates cyclin B degradation. These observations suggest that the SAC monitors stretching of kinetochores rather than centromeres and that kinetochore stretching promotes silencing of the SAC signal.